MANAJEMEN STRATEGI PENANAMAN DISIPLIN KELAS - Fajar Siregar, Ahmad Surya; Adha, Akhyar; Febiola, Elisa (PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM, 2022)
Class discipline is a very important thing that must be done and owned by every student. It aims to create a good and comfortable learning atmosphere, so that the learning process can run well. Instilling discipline needs to be done as early as possible, so that students get used to being disciplined wherever they are, even though they are not in class. The purpose of this study is to describe the strategy for instilling class discipline. In this study using the method of literature study with a qualitative approach, which comes from books, journals and other scientific articles. The results of this study indicate that instilling discipline in students is needed so that students can get used to being disciplined. The teacher is someone who is an example to students who are expected to be able to have good strategies to instill discipline in students.